Glycine betaine, an osmotic effector in Klebsiella pneumoniae and other members of the Enterobacteriaceae. - Le Rudulier, D (1983)
Osmoregulation was examined in members of the Enterobacteriaceae. Exogenous glycine betaine at a concentration as low as 1 mM was found to stimulate the growth rate of Escherichia coli, Salmonella typhimurium, and Klebsiella pneumoniae in media of inhibitory osmotic strength. The stimulation was shown to be independent of any specific solutes, electrolytes, or nonelectrolytes. Therefore, the stimulatory effect of glycine betaine was a consequence of high osmotic potential. This effect was found to be far greater than the proline effect previously observed in S. typhimurium. Whereas nitrogen fixation by K. pneumoniae is completely inhibited under conditions of osmotic stress, nitrogenase activity could be partially restored by the addition of exogenous glycine betaine to the culture medium. Furthermore, glycine betaine in combination with proline, especially proline produced internally at a high level because of regulatory mutations affecting proline biosynthesis, strongly stimulated nitrogen fixation activity during osmotic stress. Glycine betaine was accumulated by the cells, and the amount taken up was correlated with the osmolarity of the medium. These findings are discussed in relation to the possible mechanisms by which glycine betaine might cause enhanced osmotolerance.